2020
DOI: 10.1155/2020/8925420
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Hub Genes and miRNAs in Dilated Cardiomyopathy

Abstract: Purpose. The aim of this study is to identify hub genes and miRNAs by the miRNA-mRNA interaction network in dilated cardiomyopathy (DCM) disease. Methods. The differentially expressed miRNAs (DEMis) and mRNAs (DEMs) were selected using data of DCM patients downloaded from the GEO database (GSE112556 and GSE3585). Gene Ontology (GO) pathway analysis and transcription factor enrichment analysis were used for selecting DEMis, and the target mRNAs of DEMis were filtered by using miRDB, miRTarBase, and TargetScan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, Huang et al found that PIK3R1, which is up-regulated in DCM tissues, may be involved in the pathogenesis of DCM. 55 Therefore, the study of PIK3R1 in DCM may be an interesting and meaningful direction.…”
Section: Discussionmentioning
confidence: 99%
“…However, Huang et al found that PIK3R1, which is up-regulated in DCM tissues, may be involved in the pathogenesis of DCM. 55 Therefore, the study of PIK3R1 in DCM may be an interesting and meaningful direction.…”
Section: Discussionmentioning
confidence: 99%
“…miR-144-3p, having the highest statistical signi cance in EVs, is crucial for cardiac function as its loss worsened heart failure phenotype resulting with impaired late remodeling and decreased LVEF 44 . Moreover, mir-144 was identi ed as an important regulatory node in DCM 45 and its expression was down-regulated both in samples from DCM patients and in a doxorubicin-induced rodent model of cardiomyopathy 46 . Another study supporting important role of mir-144 shows that its loss resulted in ventricular dilation and impaired contractility, whereas intravenous delivery of this miRNA reduced infarcted area and improved cardiac function including LV fractional shortening, end-systolic volume, end-diastolic volume and ejection fraction 47 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-770 was constructed as the core in ceRNA network, while the upstream circRNAs, including 6:37353557|37364143, and lncRNAs, such as MSTRG.137663.1, MSTRG.77826.15, MSTRG.131343.148, MSTRG.80502.2, and Gm10734-201, acted as sponge to regulate Zfp831, Map3k6, Fosb, Pik3r5, Rhoh, et al Previous studies shown miR-770 is the potential candidates for investigating the aging process by control Wnt/chemokines and cytokines-related in ammation signaling pathways [40]. And miR-770 was also believed to play critical roles in the development and pathological mechanisms of dilated cardiomyopathy [41]. In our ceRNA network, Zfp831 and Rhoh, the downstream target of miR-770, have been identi ed to play critical roles in the differentiation of T follicular helper cells and T cells [42,43].…”
Section: Discussionmentioning
confidence: 99%